Successful aging [large type] : a neuroscientist explores the power and potential of our lives - Levitin, Daniel J (Random House Large Print, 2020)
"Author of the iconic bestsellers This Is Your Brain on Music and The Organized Mind, Daniel Levitin turns his keen insights to what happens in our brains as we age; why we should think about health span, not life span; and, based on a rigorous analysis of neuroscientific evidence, how you can make the most of your seventies, eighties, and nineties today, no matter how old you are now"--